DEVELOPMENT AND VALIDATION OF SUSTAINABLE ORGANIC FILTERS: TECHNOLOGICAL INNOVATION FOR WATER TREATMENT IN VULNERABLE COMMUNITIES - Rawell, Mayane (Health and Society, 2025)
Access to safe and potable water constitutes a fundamental human right and the basis for global public health; however, billions of people, especially in vulnerable communities in developing countries, still lack this essential resource. This article proposes the development and validation of an innovative, low-cost organic filter model, based on plant biomaterials, with an emphasis on applying Moringa oleifera seeds as a coagulant and adsorbent agent in decentralized purification systems, also known as Point-of-Use (POU) systems. The research aims to integrate technological, environmental, and social aspects, proposing a hybrid methodology that combines rigorous laboratory analyses for optimizing and validating filter efficiency with a detailed protocol for field studies, assessing the impact of adopting this technology in schools and low-income communities. The focus is on improving critical water potability indicators, including turbidity, apparent color, pH, and microbiological contamination (total coliforms and Escherichia coli), and the consequent potential reduction in the incidence of waterborne diseases, particularly acute diarrhea that disproportionately affects children under five years old. The proposed methodological approach includes the detailed physicochemical characterization of biomaterials, coagulation-flocculation tests (Jar Test), multi-stage filtration efficiency tests, and a Life Cycle Assessment (LCA) to holistically evaluate the environmental sustainability of the solution. It is expected to demonstrate, based on robust existing scientific literature and consolidated empirical evidence, that the use of biomaterials in sanitary engineering, exemplified by Moringa oleifera, constitutes a viable, scalable, low-environmental-impact, and socially impactful alternative for achieving Sustainable Development Goal 6 (SDG-6), promoting equitable access to potable water and basic sanitation in contexts of socioeconomic vulnerability and strengthening community resilience against the challenges posed by climate change and the degradation of water resources.